What Drives the Choices of Corporate Social Responsibility (CSR) Activities in Ghana: A Study of Seven Media Institutions - Antwi, Y.S. (University of Ghana, 2019)
This study examined the drivers of the choices of Corporate Social Responsibility (CSR) activities by media institutions in the Ghana. It also investigated the nature and processes of CSR engagement by these institutions. Carroll (1991)’s CSR pyramid model and the systems theory provided conceptual logic, methodological insight and scholarly critique for the study. A qualitative approach, entailing in-depth interviews with managers of CSR departments in seven media institutions, was used in data collection and analyses. The study found that CSR activities in Ghanaian media institutions were incidental, pre-programmed or built into the institutional structures and routines. Furthermore, CSR initiatives were instigated and inspired by various departments in the institution, but carried out as projects of the entire institution. The study also revealed that the types of CSR activities organized by the media were activities in areas of health, education, sports, religion, community development and awareness creation all of which can be grouped into two focus areas: community development and capacity building. The drivers of the choices of CSR activities, according to the findings, of this study were factors either internal or external to media institutions. The internal drivers were: the desire to be a responsible business, philosophy of the institution, values of Chief Executive Officers or top management and sensitivity to internal stakeholders. The external drivers were: competition, responsiveness to external stakeholders and bridging gaps in governance. In addition to emphasizing the ethical and philanthropic dimensions of CSR, this study recommends that media institutions focus on the economic imperative of CSR that demands that they are viable and profitable in their operations to be able to provide significant benefits to internal stakeholders (employees).
Thesis (MA)- University of Ghana
Keywords: Corporate Social; Choices; Seven Media; Institutions; Drives